A New Tridentate Sulfur Receptor as a Highly Sensitive and Selective Fluorescent Sensor for Cu2+ Ions. Issue 11 (22nd July 2013) - She, Haiying; Song, Fengling; Xu, Juan; Xiong, Xiaoqing; Chen, Gengwen; Fan, Jiangli; Sun, Shiguo; Peng, Xiaojun
Abstract: The introduction of Lawesson′s reagent into a bis‐rhodamine spirolactam system afforded a new fluorescent sensor for Cu 2+ ions, SRR, which contained a new tridentate sulfur ligand. SRR showed excellent specificity for Cu 2+ ions over other cations (including Cu +, Hg 2+, and Fe 3+ ), very high sensitivity (10 nM ), and a rapid response time (3 min). The detection mechanism was investigated by 1 H NMR, 13 C NMR, 31 P NMR, and ESR spectroscopy, MS, and Gaussian calculations. Coordination of a Cu 2+ ion to the tridentate sulfur ligand, which promotes ring‐opening of the rhodamine groups, followed by a spontaneous reduction reaction (Cu 2+ into Cu + ), has been proposed as the sensing mechanism. Abstract : Yes SRR! A fluorescent sensor with a new tridentate sulfur receptor, SRR, shows excellent specificity for Cu 2+ ions over other cations (including Cu +, Hg 2+, and Fe 3+ ), very high sensitivity (10 nM ), and a rapid response time (3 min). The coordination of Cu 2+ ions by the tridentate receptor to promote ring‐opening of the rhodamine groups, followed by spontaneous reduction (Cu 2+ →Cu + ), is proposed as the sensing mechanism.